Do energy reserves and cold hardiness limit winter survival of Culex pipiens - Rozsypal, Jan; Moos, Martin; Rudolf, Ivo; Košťál, Vladimír (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2021)
The risks of depletion of energy reserves and encountering lethally low temperatures are considered as two important mortality factors that may limit winter survival of mosquito, Culex pipiens f. pipiens populations. Here we show that the autumn females carry lipid reserves, which are safely sufficient for at least two overwintering periods, provided the females diapausing at temperatures typical for underground spaces (0 °C - 8 °C) would continuously rest at a standard metabolic rate (SMR). The overwintering females, however, switch from SMR to much higher metabolic rate during flight, either seeking for optimal microhabitat within the shelter or in response to disturbances by air current or predator attack. These behaviors result in fast oxidation of lipid reserves and, therefore, the autumn load of energy reserves may actually limit winter survival under specific circumstances. Next, we show that the level of females' cold hardiness is physiologically set relatively weak for overwintering in open field, above-ground habitats, but is ecologically entirely sufficient for overwintering in most underground spaces. The characteristics of suitable overwintering shelters are: no or limited risk of contact with ice crystals, no or limited air movements, winter temperatures relatively stable between +2 and + 6 °C, winter minimum does not drop below -4 °C for longer than one week, or below -8 °C for longer than 1 day.
Keywords: metabolismus lipidů; Animals; energetický metabolismus; Female; Seasons; zvířata; Lipid Metabolism; nízká teplota; Culex; Energy Metabolism; diapauza; roční období; ženské pohlaví; Diapause; Cold Temperature